Comparison of Social Media Video Acceptance for Health Knowledge in Generation Z Using TAM - Shanti Putri Syawalina; Arista Pratama; Eristya Maya Safitri (Komunitas Dosen Indonesia, 2025)
The development of information and communication technology has changed the way Generation Z accesses knowledge, with social media such as Instagram and TikTok being the main sources of information. However, challenges arise as health content is often mixed with entertainment content, making the validity of the information delivered difficult to ascertain. Therefore, an evaluation of both platforms is needed to assess their effectiveness and the benefits received by users. This study aims to evaluate the acceptability of videos as a source of health knowledge on Instagram and TikTok using the Technology Acceptance Model (TAM). The main focus was to identify factors that influence the acceptance of health video content and compare the effectiveness of the two platforms. Data was collected from 600 respondents through purposive sampling technique and analyzed using PLS-SEM method. The results showed that the majority of respondents preferred TikTok as a source of health information compared to Instagram. Content Richness affects Users Satisfaction. In addition, Flow State and Personal Innovativeness affect Perceived Ease of Use and Perceived Usefulness. These three variables also influence the acceptability of health video content on Instagram and TikTok. These findings suggest the importance of engaging and informative content to improve Generation Z's health knowledge.